2017
DOI: 10.20950/1678-2305.2017v43n2p231
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho produtivo, hematologia e crescimento muscular de tilapia do nilo alimentadas com isoleucina

Abstract: O objetivo desse estudo foi avaliar a exigência dietética de isoleucina para juvenis de tilápia do Nilo com base no desempenho produtivo, respostas hematológicas e bioquímicas e crescimento muscular. Trezentos juvenis de tilápia do Nilo (18,09 ± 0,11g) foram distribuídos em 20 tanques de fibra de vidro e alimentadas com cinco rações extrusadas isoproteicas (280 g kg-1 de proteína bruta) e isoenergéticas (3000 kcal kg-1) as dietas foram formuladas continham 7,00; 8,18; 9,35; 10,53 e 11,70 g kg-1 de isoleucina. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
5
8
0
2
Order By: Relevance
“…Myo bers hyperplasia and hypertrophy could partly be re ected by the frequency of myo bers diameter [71]. The frequency of myo ber smaller than 20 μm indicated hyperplasia, that frequency of myo ber lager than 50 μm denoted hypertrophy [59,72]. In the current study, the percentage of myo ber with diameters smaller than 20 μm and larger than 50 μm signi cantly rose in sh fed dietary Ile.…”
Section: Dietary Ile Improved Myo Ber Hyperplasia and Hypertrophysupporting
confidence: 49%
See 1 more Smart Citation
“…Myo bers hyperplasia and hypertrophy could partly be re ected by the frequency of myo bers diameter [71]. The frequency of myo ber smaller than 20 μm indicated hyperplasia, that frequency of myo ber lager than 50 μm denoted hypertrophy [59,72]. In the current study, the percentage of myo ber with diameters smaller than 20 μm and larger than 50 μm signi cantly rose in sh fed dietary Ile.…”
Section: Dietary Ile Improved Myo Ber Hyperplasia and Hypertrophysupporting
confidence: 49%
“…In the current study, the percentage of myo ber with diameters smaller than 20 μm and larger than 50 μm signi cantly rose in sh fed dietary Ile. However, a study in Nile tilapia juveniles showed dietary Ile exhibited a non-effect in the frequency of myo ber diameter [59]. The discrepancies results may be due to the differences in sh species, feeding management, and age.…”
Section: Dietary Ile Improved Myo Ber Hyperplasia and Hypertrophymentioning
confidence: 97%
“…In the present study, fish fed 12.5 g/kg diet increased muscle crude protein and lipid contents, indicating that dietary Ile could improve the flesh nutritional quality. Previous studies have shown that dietary Ile could significantly increase muscle crude protein and fat contents in grass carp [ 9 ] and Nile tilapia ( Oreochromis niloticus ) [ 59 ]. Besides, flesh quality is also strongly regulated by physicochemical and texture characteristics, which are the most important aspects of attracting approach to consumers [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ile, one of BCAA, have been reported the importance of effecting fish growth performance [ 9 , 14 , 59 ]. Fish growth is mainly determined by muscle growth, which constitutes the major edible sources of the fillet [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation